Enemy Inside - Hunter, Scott (Thornton, CO Scott Hunter, 2020)
DCI Brendan Moran's morning is interrupted whena suicidal ex-soldier threatens to jump from a multi-storey car park ...Moran soon regrets getting involved when an unexpected visitor turns up on his doorstep toconfront him with what appears to be damning evidence of his past misconduct.Can the Irish Detective clear his name, or must he come clean and face the consequences?One thing seems certain: by the time the night is over, his reputation may not be the only casualty ...
Keywords: Crime Thrillers; International Mystery & Crime